A study on the effectiveness of the recruitment and selection process of Square Food and Beverage Limited - Kabir, Seefat Binte (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.